Produção e caracterização de filmes compósitos de poliestireno e cintiladores para aplicação em detectores de radiação - Coura, Rayssa Lima Costa (2022)
In this work, self-sustainable composite films based on BaF2 and LiYF4:Ln3+ (Ln = Tb, Ce) particles, embedded separately, in polystyrene (PS) matrix were produced. The fluorides were synthesized through the microwave-assisted hydrothermal method. The crystalline phases of powders were characterized by X-ray diffraction (XRD). The morphology and particles size were investigated by scanning electron microscopy (SEM), revealing the formation of nanometric particles for BaF2 and micrometric particles for LiYF4. For PS and BaF2 films, photoluminescence (PL) analysis showed that self-trapped excitons of BaF2 nanoparticles incorporated into the polymeric matrix are excited at 5.6 eV, due to a synergistic effect, involving antenna effect and Förster energy transfer. From chromatic coordinates it was possible to observe that the light emission can be tuned to different shades of colors between blue and green, making the films useful for new applications on light emitting devices. For PS and LiYF4:Ln3+ films, photoluminescence results showed that codoping with Ce,Tb leads to a strong increase in green emission of Tb. This emission is suitable to the spectral sensitivity of charge coupled devices (CCD) image sensor. Radioluminescence (RL) measurements were performed in order to investigate the efficiency of light output under X-ray excitation. The microstructure fracture cross-section of the films was performed by scanning electron microscopy, energy dispersive X-ray spectroscopy (EDS), X-ray fluorescence (XRF) and X-ray excited optical luminescence (XEOL) mapping. The images showed that concentration of polystyrene precursor solution affects the scintillator distribution on the film body influencing, consequently, the efficiency of emission process. The results indicate that the films are potential candidates for use in scintillator devices with high efficiency.